2014
DOI: 10.3892/etm.2014.2149
|View full text |Cite
|
Sign up to set email alerts
|

Intracisternal administration of an interleukin-6 receptor antagonist attenuates surgery-induced cognitive impairment by inhibition of neuroinflammatory responses in aged rats

Abstract: Postoperative cognitive dysfunction (POCD) is common in elderly patients, and may persist or even evolve into Alzheimer’s disease. It has been hypothesized that POCD is mediated by surgery-induced inflammatory processes. As a pro-inflammatory cytokine, the detailed role of interleukin (IL)-6 in POCD remains largely unknown. In this study, laparotomy was used to mimic human abdominal surgery in aged Sprague-Dawley rats. It was found that memory and learning were impaired following surgery, accompanied by the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Production of inflammatory related cytokines was also investigated to identify the M1/M2 phenotypic microglia from the viewpoint of functions. IL-6 has been considered an important pro-inflammatory cytokine in pathogenesis of POCD [ 37 ]. Furthermore, IL-6 is thought to be secreted specifically by M1 microglia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Production of inflammatory related cytokines was also investigated to identify the M1/M2 phenotypic microglia from the viewpoint of functions. IL-6 has been considered an important pro-inflammatory cytokine in pathogenesis of POCD [ 37 ]. Furthermore, IL-6 is thought to be secreted specifically by M1 microglia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 IL-6 has been suggested as playing a crucial role in the neuroinflammatory response leading to POCD. 130 Inflammatory cytokines have also been associated with POCD after cardiac surgery 131 and levels of S-100, an indicator of traumatic brain injury, was found to be an indicator of POCD. 132,133 In addition, in a meta-analysis of studies investigating the inflammatory response of patients, IL-6 and S-100B were identified as being correlated with POCD.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…Animal studies demonstrated that the pathophysiological process of PND might be related to the inflammatory cytokines TNF-α, IL-1β, and IL-6 in the hippocampus (Tang et al, 2011; Hovens et al, 2014; Wang et al, 2017). The rodent experiments showed that the inhibition of the expression of central proinflammatory cytokine signaling can lower the severity of postoperative memory impairment (Cibelli et al, 2010; Terrando et al, 2010; Barrientos et al, 2012; Jiang et al, 2015). Further studies demonstrated that mTOR expression is vital in facilitating neuroinflammation in many neurodegenerative diseases (Soltani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%